Maintenance gold fish (carassius auratus) with different Feed on recirculation systems - M. Husnan; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from June 30 to July 30 2014, for 30 days inAquaculture Technology Laboratory of Fisheries Faculty and Marine Sciences,University of Riau Pekanbaru. This study aimed to determine the effect of type offeeding is best to fish growth and survival of comets in the recirculation system.The method used in this study was a laboratory-scale experimental methods withexperimental design completely randomized design (CRD) with three treatmentswere given treatment level is P1 = Tubifex sp, Moina sp = P2, and P3 = artificialPellets. The best result was treatment P1 treatment using feed tubifex sp absoluteweight of 2.5 grams and a length of 3.8 cm absolute. Survival and body colorcomet fish best at using P2 feed moina sp.Keyword : Gold fish (Carassius auratus), feed,recirculation